Validity of Electronic Module Based on Process Oriented Guided Inquiry Learning (POGIL) Model to Train Students' Science Process Skills - S. A. Oktaria; M. Rahmad; L. Anwar (Journal of Science Education Research, 2023)
The research aimed to validate the electronic module (e-module) based on the process oriented guided inquiry learning (POGIL) model on the topic of Vibrations, Waves, and Sounds in junior high school. The e-module developed was expected to help students learn independently and practice the science process skills. The research method was a research and development in accordance with the Plomp (2013) model. There were three validation components in the developed e-module\, i.e.: material, pedagogical, and media validation. This e-module has been validated based on the average assessment score given by the validators. The validation results of the material, pedagogical, and media were in a very valid category, with a percentage of 91.6%, 88.9%, and 89.8%, respectively. In short, the developed e-module produced excellent assessment results. Moreover, it was feasible for use in the science learning process of junior high school and can train students' science process skills